Lower Extremity Blood Flow Velocity in Obese versus Nonobese Pregnant Women - Dutta, Eryn H.; Burns, Ralph N.; Pacheco, Luis D.; Marrs, Caroline C.; Koutrouvelis, Aristides; Koutrouvelis, Gayle L. Olson (American Journal of Perinatology, 2020)
Objective Obesity and pregnancy are risk factors for venous thromboembolism (VTE). In nonpregnant individuals, abdominal obesity is associated with venous insufficiency. This study aimed to compare venous Doppler volume flow and velocity in the lower extremities of obese versus nonobese women.Study Design A prospective cohort study was performed. Duplex ultrasound examined bilateral lower extremity venous flow and velocity (time-averaged mean velocity, TAMV). Flow was analyzed at the superficial femoral (SFV), distal external iliac (DEI), common femoral, profunda femoris, and popliteal veins. Mann–Whitney U-test, Spearman's correlation, and chi-square tests were used, with a significance of p < 0.05.Results Left SFV TAMV and volume flow were higher in the obese group (5.1 [4.1–5.7] vs. 2.8 [1.7–3.4] cm/second; p < 0.001) and (89 [73–119] vs. 48 [26–62] cm/minute; p = 0.005). Significant differences were noted for right DEI flow (obese 326 [221–833] vs. nonobese 182 [104–355] cm/minute; p = 0.049). The right femoral profunda flow was also higher in obese (49 [40–93] cm/minute) compared with nonobese (31 [22–52] cm/minute; p = 0.041).Conclusion Volume flow and TAMV in the lower extremities of obese gravidas are higher compared with nonobese ones. Thus, the increased risk of VTE among obese pregnant women may not be caused by venous stasis.
Keywords: blood flow velocity in pregnant women; obesity in pregnancy; venous doppler volume flow and velocity